Differential metabolic and coexpression networks of plant metabolism. (May 2015) - Omranian, Nooshin; Kleessen, Sabrina; Tohge, Takayuki; Klie, Sebastian; Basler, Georg; Mueller-Roeber, Bernd; Fernie, Alisdair R.; Nikoloski, Zoran
Highlights: We examine the conclusions from different network-based analyses of plant metabolism. Specialized and nonspecialized plant metabolisms have different coexpression patterns. Abstract : Recent analyses have demonstrated that plant metabolic networks do not differ in their structural properties and that genes involved in basic metabolic processes show smaller coexpression than genes involved in specialized metabolism. By contrast, our analysis reveals differences in the structure of plant metabolic networks and patterns of coexpression for genes in (non)specialized metabolism. Here we caution that conclusions concerning the organization of plant metabolism based on network-driven analyses strongly depend on the computational approaches used.